Holomorphicity of totally geodesic Kobayashi isometry between bounded symmetric domains - Kim, Sung‐Yeon; Seo, Aeryeong (Journal of the London Mathematical Society, 2024)
In this paper, we study the holomorphicity of totally geodesic Kobayashi isometric embeddings between bounded symmetric domains. First, we show that for a ‐smooth totally geodesic Kobayashi isometric embedding where , are bounded symmetric domains, if is irreducible and or more generally, for any tangent vector of , then is either holomorphic or anti‐holomorphic. Second, we characterize Kobayashi isometries from a reducible bounded symmetric domain to itself.